Revision of the Afrotropical Lycorininae (Ichneumonidae; Hymenoptera) II. Three new Lycorina species and additional distribution records - Rousse, P.; Noort, S. Van (Zootaxa, 2014)
Three new Afrotropical Lycorina species are described: L. horstmanni sp. nov., L. jacksonfive sp. nov. and L. riftensis sp. nov. The description of L. globiceps is expanded to include the large variability of the colour pattern. New distribution records are provided for L. fici and L. globiceps. An illustrated dichotomous key, and an online interactive matrix key available on www.waspweb.org, are provided for the identification of the seven known Afrotropical Lycorininae species.